Irrigation timing and nitrogen fertilization for common bean crop in the cerrado region - Guerra, Antônio Fernado; Silva, Dijalma Barbosa da; Rodrigues, Gustavo Costa (Pesquisa Agropecuaria Brasileira, 2000)
This study was carried out in the experimental field of the Embrapa-Centro de Pesquisa Agropecuária dos Cerrados (CPAC) to determine the irrigation timing and the nitrogen amounts for common bean crop (Phaseolus vulgaris L.), cultivated after corn, in the cerrado region. Water was applied when soil-water tension, measured at a depth of 10 cm reached values of 41, 55, 75 and 300 kPa. The nitrogen doses were splited in two applications. Half doses was applied just after germination and the other half at the initial flowering stage. The highest yield was obtained with irrigation at 41 kPa, measured at a depth of 10 cm. In relation to nitrogen doses, maximum yield was attained with variable soil water tension value used to control water application. The total amount of water applied to common bean crop for a yield over 4,800 kg/ha was approximately 450 mm. The value of the relationship between yield and applied water increased as soil water tension and nitrogen doses increased.